Reexamining the Association Between Smoking and Periodontitis in the Dunedin Study With an Enhanced Analytical Approach. Issue 10 (1st October 2014) - Zeng, Jiaxu; Williams, Sheila M.; Fletcher, David J.; Cameron, Claire M.; Broadbent, Jonathan M.; Shearer, Dara M.; Thomson, W. Murray
Abstract : Background: Smoking is a major risk factor for periodontal disease. Conventional oral epidemiology approaches have found strong, consistent associations between chronic smoking and periodontal attachment loss (AL) through ages 26, 32, and 38 years, but those statistical methods disregarded the data's hierarchical structure. This study reexamines the association using hierarchical modeling to: 1) overcome the limitations of an earlier approach (trajectory analysis) to the data and 2) determine the robustness of the earlier inferences. Methods: Periodontal examinations were conducted at ages 26, 32, and 38 years in the Dunedin Multidisciplinary Health and Development Study. The number of participants examined at those three ages were 913, 918, and 913, respectively. A generalized linear mixed model with a quasi‐binomial approach was used to examine associations between chronic smoking and periodontal AL. Results: At ages 26, 32, and 38, smokers had 3.5%, 12.8%, and 23.2% greater AL than non‐smokers. Regular cannabis use was associated with greater AL after age 32, but not at age 26. Males had more AL than females. Participants with high plaque scores had consistently greater AL; those who were of persistently low socioeconomic status had higher AL at ages 32 and 38, but not at age 26. The amount of AL in anterior teeth was less than in premolars and molars. Gingival bleeding was associated with higher AL at ages 26, 32, and 38. Conclusion: The smoking–periodontitis association is observable with hierarchical modeling, providing strong evidence that chronic smoking is a risk factor for periodontitis.